Financial Performance and Firm Value: The Moderating Role of ISO 9001:2015 Tenure in Indonesian Non-Financial Firms - Danis Islamiyatul Vivi; Indah Yuliana (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Current Ratio (CR), and Debt-to-Equity Ratio (DER) on firm value, with the duration of ISO 9001:2015 certification (ISO tenure) as a moderating variable, among non-financial sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employs a quantitative approach using secondary data obtained from companies’ financial statements and ISO certification documents. The sampling technique utilized purposive sampling, involving 69 companies or 345 observations. Data analysis was conducted using panel data regression and Moderated Regression Analysis (MRA) with a Random Effects Model (REM). The results indicate that ROA has a positive and significant effect on firm value, whereas CR and DER do not have a significant effect. Furthermore, ISO tenure moderates the effect of ROA on firm value but does not moderate the effects of CR and DER. The novelty of this study lies in the use of the duration of ISO 9001:2015 certification as a moderating variable in the relationship between financial performance and firm value. These findings suggest that consistent implementation of a quality management system strengthens the impact of profitability on firm value growth.